2014
DOI: 10.1016/j.jcrs.2014.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure profiles during femtosecond laser–assisted cataract surgery

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 10 publications
2
32
2
3
Order By: Relevance
“…Furthermore, intravitreal measurements showed a delayed increase in pressure during vacuum application. Nevertheless, discrepancies between ICP and IVP levels during FLACS are well known and described earlier,16 results should be considered carefully due to possible limitations of the ex vivo experimental set-up and the intravitreal measurement concept itself. One could possibly assume an impairment of the intravitreal IOP measurements caused by an occlusion of the intravitreal cannula initiated by the gel-like consistency of the natural vitreous body.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, intravitreal measurements showed a delayed increase in pressure during vacuum application. Nevertheless, discrepancies between ICP and IVP levels during FLACS are well known and described earlier,16 results should be considered carefully due to possible limitations of the ex vivo experimental set-up and the intravitreal measurement concept itself. One could possibly assume an impairment of the intravitreal IOP measurements caused by an occlusion of the intravitreal cannula initiated by the gel-like consistency of the natural vitreous body.…”
Section: Discussionmentioning
confidence: 88%
“…In the Victus platform, a relative rise of 25 mm Hg was observed,16 while published values for the Catalys platform which uses a liquid interface range from 25.9 mm Hg to 32.4 mm Hg 17 18…”
Section: Discussionmentioning
confidence: 93%
“…Using a Tono-Pen Avia (Reichert Technologies, Depew, NY, USA), Baig et al 11 utilized a different femtosecond cataract laser platform with a multipiece curved interface to also perform IOP measurements on humans. Mean IOP was reported to rise to 42.1 6 10.8 mm Hg after the femtosecond procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all the in vivo studies reported IOP elevations after femtosecond laser treatment, whereas we did not find any such elevations in the experimental setup of the present study after the eye was fully disconnected from the LOI. 6,8,9,11 There are probably different causes of the IOP increases during the different steps of the FLACS procedure. As shown in Figures 2 and 3, a significant change occurs immediately after placing the patient interface on the enucleated eye.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Abell ve ark.nın yaptığı 4.080 gözü içeren büyük bir çalışmada; Catalyst Lazer Sistemi ile cerrahi olan 1.852 gözden 21'inde tamamlanmamış kapsülotomi saptandı. Arka kapsül yırtığı FSL ile cerrahi olan 8 gözde gelişirken, FSL olmayan 4 gözde meydana geldi (İstatistiksel olarak anlamlı değildi).…”
Section: Di̇ğer Kompli̇kasyonlarunclassified